Editor’s Note: Is the Multiple Intelligences Theory a Research-Based Theory or a Story with a Positive Message? - Allan Leslie White (SEAMEO Regional Centre for QITEP in Mathematics, 2019)
Howard Gardner introduced his Theory of Multiple Intelligences in 1983. It is a model of intelligence which differentiates intelligence into various specific (primarily sensory) modalities, rather than being dominated by a single general ability such as IQ. The Theory of Multiple Intelligences has attracted controversy and criticism among the research community but has resonated with teachers and many educationalists who have supported the practical value of various educational approaches suggested by the Theory of Multiple Intelligences. This paper will investigate claims that the Multiple Intelligences Theory is a research-based theory, or as critics have claimed, it is a good story with a positive message.